Impact of heat stress on blood serum cortisol level in dairy cows - R. V. Mylostyvyi; M. Wrzecińska; M. Samardžija; B. V. Gutyj; V. H. Yefimov; P. М. Skliarov; M. O. Lieshchova (Theoretical and Applied Veterinary Medicine)
Heat stress (HS) is a critical environmental factor that disrupts the hormonal balance of animals by activating and subsequently suppressing the hypothalamic-pituitary-adrenal (HPA) axis. This process alters cortisol secretion, a key stress hormone involved in maintaining homeostasis, regulating metabolism, and facilitating adaptation to adverse conditions. This study investigates the impact of HS on the hormonal responses of Holstein and Brown Swiss dairy cows, with a specific focus on cortisol as a principal biomarker of stress adaptation. The research was conducted under conditions of acute and chronic HS of moderate intensity. Cows were divided into control (CON) and experimental (HYP) groups. Serum cortisol levels were assessed while accounting for the temperature-humidity index (THI), lactation number, days in milk, and energy-corrected milk yield. Cortisol concentrations were measured in blood serum with using an electrochemiluminescence immunoassay method (ECLIA). The findings revealed that cows in the experimental groups experienced significantly higher daily temperatures and THI compared to the control groups. Holstein cows were subjected to chronic HS for 45 days, with a mean THI of 77.5, while Brown Swiss cows experienced acute HS for 5 days, with a mean THI of 77.6. Serum cortisol levels were significantly lower in the experimental groups: 27.25 ± 2.92 nmol/L versus 39.45 ± 3.26 nmol/L (a 30% decrease) in Holstein cows and 11.6 ± 0.54 nmol/L versus 24.5 ± 8.85 nmol/L (a 52% decrease) in Brown Swiss cows (p < 0.05), indicating a suppressive effect of HS on the HPA axis. These results highlight the importance of breed-specific differences in stress responses and underscore the role of cortisol as a key indicator of adaptive mechanisms. The observed reduction in cortisol concentrations suggests potential effects of HS on metabolic stability and resilience to environmental stressors.